Implementation of Education Quality Improvement in Primary Schools Judging From Teacher Competency Test in Sukabumi Regency - Nurjanah, Erni; Sofiawati, Esmi Tsalsa (International Journal for Educational and Vocational Studies, 2019)
This study aims to understand the extent of the Teacher Competency Test results which include: (a) pedagogical competencies, (b) personality competencies for improving the quality of education in Cilangla State Elementary School, Gandasoli State Elementary School, and Babakan Pamoyanan Elementary School in Sukabumi District. This research uses a qualitative approach that produces descriptive data with case study methods. The results of this study indicate that there are obstacles that occur in the implementation of Teacher Competency Tests, namely the extent of the material being tested, especially in the aspects of pedagogical competence, professional competence and lack of mastery in the operation of the teacher's computer. This is what causes the low scores obtained when implementing the Teacher Competency Test. But on the other hand in improving the quality of education, teachers continue to strive to be able to deliver their students to obtain various achievements in school.